The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1128/mcb.01760-06
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 Is a Direct Target of the Transcription Factor E2F1 during Cerebral Ischemia-Induced Neuronal Death In Vivo

Abstract: The nuclear transcription factor E2F1 plays an important role in modulating neuronal death in response to excitotoxicity and cerebral ischemia. Here, by comparing gene expression in brain cortices from E2F1 ؉/؉ and E2F1 ؊/؊ mice using a custom high-density DNA microarray, we identified a group of putative E2F1 target genes that might be responsible for ischemia-induced E2F1-dependent neuronal death. Neuropilin 1 (NRP-1), a receptor for semaphorin 3A-mediated axon growth cone collapse and retraction, was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…Therefore, these data indicate that E2F1 downregulates the expression level of pro-angiogenic VEGF xxx transcripts. To test whether this effect was specific for VEGF xxx transcripts, we analysed the expression level of neuropilin-1, the co-receptor of VEGFR-2 that was recently identified as a new E2F1 transcriptional target gene (Jiang et al, 2007). Upon E2F1 overexpression, we found that the level of neuropilin-1 mRNA was slightly increased, whereas the expression of neuropilin-2 was not affected (Figure 1a, lower panel).…”
Section: E2f1 Downregulates the Expression Of Pro-angiogenic Vegf XXXmentioning
confidence: 92%
“…Therefore, these data indicate that E2F1 downregulates the expression level of pro-angiogenic VEGF xxx transcripts. To test whether this effect was specific for VEGF xxx transcripts, we analysed the expression level of neuropilin-1, the co-receptor of VEGFR-2 that was recently identified as a new E2F1 transcriptional target gene (Jiang et al, 2007). Upon E2F1 overexpression, we found that the level of neuropilin-1 mRNA was slightly increased, whereas the expression of neuropilin-2 was not affected (Figure 1a, lower panel).…”
Section: E2f1 Downregulates the Expression Of Pro-angiogenic Vegf XXXmentioning
confidence: 92%
“…For example, in HeLa cells NRP-1 expression is controlled by SP1, AP1, and CCAAT box transcription factors, 42 whereas in neurons E2F1 factor binds directly to the endogenous NRP-1 promoter to positively regulate its expression. 43 Production of SHH ligand and pathway activity is related to NRP-1 expression, and NRP-1 knockdown leads to reduced SHH, Gli-1, and E-cadherin production in renal carcinoma cells. 26 Similarly, blockade of the SHH pathway leads to reduced expression of E-cadherin, b 1 integrin, and VEGF in EOC cells.…”
Section: Vegfr2 Rnai Knockdown Increases Eoc Malignancy Sai Adham Et Almentioning
confidence: 99%
“…Besides its role in regulating neuronal morphology, accumulating evidence suggests that Sema3A induces neuronal apoptosis (Gagliardini and Fankhauser, 1999;Shirvan et al, 1999Shirvan et al, , 2002Ben-Zvi et al, 2006). Despite recent progress, whether Sema3A, Npn1 and plexins are physiologically relevant in developmental cell death in vivo, and the mechanisms underlying semaphorin-induced apoptosis, remain poorly understood (Ben-Zvi et al, 2006Jiang et al, 2007Jiang et al, , 2010Haupt et al, 2010). Here we identify Sema3A as a retrograde death signal for developing sympathetic neurons.…”
Section: Discussionmentioning
confidence: 94%